Customer Perceived Value Sebagai Variabel Mediasi pada Pengaruh Service Quality terhadap Customer Retention - Muhammad Aldi Saputra; Rini Safitri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this research is to analyze and explain the influence of service quality on customer retention with customer perceived value as a mediating variable for customers. The population in this research is Bank Syariah Indonesia customers. Researchers took a sample of 140 respondents using purposive sampling, with the criteria for respondents being that they had been customers of Bank Syariah Indonesia for at least 1 year, were at least 17 years old, customers were domiciled in Malang Raya, had previously used Bank Syariah Indonesia services, had repeatedly made transactions at the bank. Indonesian Sharia. The research hypothesis was tested using a Partial Least Square (PLS) approach based on the Structural Equation Model (SEM). The results obtained from this research indicate that customer perception value has a significant effect on customer retention, service quality has a significant effect on customer retention, service quality has a significant effect on customer perception value. Service quality has a significant effect on customer retention which is mediated by the full value felt by customers.